Carencia de talentos en atletismo, especialidad medio fondo, en la edad de 15 años, en el Colegio Experimental Maldobado de la cuidad de Riobamba, periodo 2011 - Álvaro Fiallos, Liliana Paola (2012)
This research was conducted in the city of Riobamba at the National Experimental School "Pedro Vicente Maldonado" where a selection of talented athletes in middle-distance tests was developed. The selection is the process by means of which the talented and gifted people are individualized as well as those who have positive attitudes towards a specific sport. This can only be successfully archieved by using a set of appropriate research methods which have been chosen involving the study of different aspects of the personality of the athlete using teaching physic methods. Modern sport is characterized by an impetuous growth of record, a considerable intensification of training loads and competition, a sharp struggle among rivals in strength. A special feature of the current period of sports development is a scientific research of young talented people capable of dealing heavy loads and high rates of sports development. It has been widespread the view that a significant sporting achievement is the result of a complex interaction between heredity and environmental influences outside.